A repeated game of self regulation - Nuñez, Javier (Estudios de Economía, 2016)
This paper analyses incentives for self-regulation of quality from a principal-agent perspective, in a context of repeated interaction between a Self-Regulatory Organization (SRO) and consumers who can not observe SRO vigilance choice or fraud perfectly. This work unveils five obstacles for positive SRO vigilance to occur in equilibrium. However, this article also shows that public regulation in parallel to Self-Regulation can enhance SRO incentives to monitor quality and reduce fraud. Therefore, defying conventional wisdom, a mix of public and self regulation may be preferred because it would benefit from SROs informational advantage about quality, while public regulation would provide the incentives to monitor quality that may be absent otherwise.